2017
DOI: 10.1089/lap.2016.0689
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Radical Nephrectomy for Large (>7 cm) Solid Renal Tumors: Comparison of Perioperative Outcomes with the Transperitoneal Approach

Abstract: Retroperitoneal LRN for a large (>7 cm) solid renal tumor demonstrated a superior result in terms of operation time, estimated blood loss, and time to start diet than transperitoneal LRN. Other perioperative outcomes and complication rate were comparable between the two approaches. We believe that with sufficient experience, retroperitoneal LRN may be an effective and safe procedure for large (>7 cm) solid renal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Blood loss in published series ranged from 0 to 828 ml. The lowest losses recorded by Oscar Schatloff et al [6] in a retrospective study including 129 patients admitted for laparoscopic nephrectomy, and the highest by Hee Youn Kim et al [7] in a comparative study of the retroperitoneal (34 patients) and transperitoneal (30 patients) pathways of laparoscopic radical nephrectomy for large solid renal tumors (> 7 cm).…”
Section: Discussionmentioning
confidence: 96%
“…Blood loss in published series ranged from 0 to 828 ml. The lowest losses recorded by Oscar Schatloff et al [6] in a retrospective study including 129 patients admitted for laparoscopic nephrectomy, and the highest by Hee Youn Kim et al [7] in a comparative study of the retroperitoneal (34 patients) and transperitoneal (30 patients) pathways of laparoscopic radical nephrectomy for large solid renal tumors (> 7 cm).…”
Section: Discussionmentioning
confidence: 96%
“…In China, RLRN is more prevalent. Kim et al previously showed that RLRN achieved better perioperative outcomes than TLRN on the premise that the mean tumor volume was larger, suggesting that RLRN was feasible in patients with >7 cm tumor ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…While a retrospective comparative study suggested improved operation times, blood loss, and time to commencement of diet with retroperitoneal LRN [12]; Recently published articles with prospective randomized series demonstrated no statistically difference in the overall operative morbidity in transperitoneal versus retroperitoneal radical nephrectomies [13][14][15][16]. Nevertheless it is remarkable that the retroperitoneal group, compared to the transperitoneal approach, was associated with a shorter total time to control the renal artery and quicker control of the renal vein [13].…”
Section: The Lower Pole Approach In Retroperitoneoscopic Radical Neph...mentioning
confidence: 99%